Ensilering i plansilo - Persson, Annica (2013)
The aim with this literature review is to describe the ensilage process in a bunker silo. The process from harvest and chopping to filling and unloading the silo is explained. The sealing of the bunker silo plays an important role for the final quality of the silage. This review covers some of the techniques used. There are many silage additives on the market, some of them are presented including how they act in the ensilage process. The process is divided into three different phases. Those are the aerobe phase, the storage phase and the feed out phase. This paper will cover what happens in the different phases, where oxygen has an important role. Silage losses during storage and feed out are common. If yeast and clostridia have the opportunity to grow there will be nutritional and dry matter losses in the silage. Means to avoid this are discussed. At last thoughts and opinions about earlier studies and about the use of silage additives and covering materials will be discussed.